ANALYSIS OF CORROSION RATE OF ASTM A 387 GRADE 12 AND A 283 GRADE FOR SULFURIC ACID TANK MATERIAL - Meryanalinda Meryanalinda; Dedy Rachman Ardian; Mochammad Shocib; Ahmad Yasin (Institut Teknologi Adhi Tama Surabaya, 2020)
Corrosion is a process of degradation metal quality which is very detrimental in the industry. Especially in an industries related to utilization of acidic liquids such assulfuric acid, hydrochloric acid, etc. If corrosion rate of carbon steel can be estimated, the prediction of remaining life of carbon steel, and the preventive methods of corrosionwould be more appropriate. This will reduce technical, economic and aesthetic losses. The aims of this study was to determine corrosion rate of carbon steel in sulfuric acid. This study used ASTM A 387 Grade 12 and ASTM A 283 Grade A carbon steel type fortank material, where one material is represented by 5 specimen. The corrosion rate of Specimens were measured by the weight loss method for 31 days. The 5 specimens were divided into 3 regions where specimens no.1 and 2 were immersed in sulfuric acid , specimens no.3 were in the middle area or zone level (partially immersed), and specimens no.4 and 5 were not immersed in sulfuric acid. The highst corrosion rate occured on specimen No.3 with maximum corrosion rate was 0,097 mm/y for ASTM A 387 Gr 12 and 0,096 mm/y untuk material ASTM A 283 Gr A. The results of corrosion rate on ASTM A 387 Grade 12 material are lower than corrosion rate of ASTM A 283 Grade A material. This is caused by presence of Mo and Cr alloy elements in ASTM A 387 Grade 12.